Cho m>0 CMR: \(|A|>m\)thì\(-m< A< m\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a.
$\frac{a}{b}<1\Rightarrow a< b\Rightarrow a-b<0$
Xét hiệu $\frac{a}{b}-\frac{a+m}{b+m}=\frac{am-bm}{b(b+m)}=\frac{m(a-b)}{b(b+m)}<0$ do $a-b<0$ và $a,b,m$ là số tự nhiên $>0$
$\Rightarrow \frac{a}{b}<\frac{a+m}{b+m}$
b.
$\frac{a}{b}>1\Rightarrow a> b\Rightarrow a-b>0$
Xét hiệu $\frac{a}{b}-\frac{a+m}{b+m}=\frac{am-bm}{b(b+m)}=\frac{m(a-b)}{b(b+m)}>0$ do $a-b>0$ và $a,b,m$ là số tự nhiên $>0$
$\Rightarrow \frac{a}{b}>\frac{a+m}{b+m}$
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có M = - a + b - b - c + a + c - a
= ( - a + a ) + ( b - b ) + ( - c + c ) - a
= 0 + 0 + 0 - a
= - a
Vì a < 0 => - a > 0
=> M > 0
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a vì a+2>5 =>a+2+(-2)>5+(-2)=>a+2>3
b vì a>3 => a+2>3+2 =>a+2>5
c vì m>n =>m-n>n-n=>m-n>0
đ vì m-n=0 =>m-n+n>0+n=>m>n
e vì m<n nên m+(-4)<n+(-4) =>m-4<n-4 (1)
vì -4>-5 => m-4>m-5 (2)
từ (1) và (2) =>m-5<n-4
![](https://rs.olm.vn/images/avt/0.png?1311)
ta có: x<y
\(\Rightarrow\frac{a}{m}< \frac{b}{m}\Rightarrow a< b\)
\(\Rightarrow a+a< b+a\)
\(\Rightarrow\frac{a+a}{2m}< \frac{a+b}{2m}\)
\(\Rightarrow\frac{2a}{2m}< \frac{a+b}{2m}\)
\(\Rightarrow\frac{a}{m}< \frac{a+b}{2m}\Rightarrow x< z\) (1)
ta có: a<b ( cmt)
=> a + b < b+b
\(\Rightarrow\frac{a+b}{2m}< \frac{b+b}{2m}\)
\(\Rightarrow\frac{a+b}{2m}< \frac{2b}{2m}=\frac{b}{m}\Rightarrow z< y\) (2)
Từ (1);(2) => x<z<y